Biomarker-validated maternal smoking and environmental tobacco smoke exposure status and its associations with perinatal outcomes - Silva, Ana Inês (2021)
Tobacco consumption and environmental tobacco smoke (ETS) are associated with an increased risk of multiple adverse perinatal outcomes. Within the framework of the NEOGENE project, the aim of this study was to validate smoking and ETS exposure status among pregnant women, to more precisely ascertain its associations with perinatal outcomes, using urinary cotinine (UC), a biomarker of tobacco smoke exposure. (...)